Inverted planar heterojunction perovskite solar cells with high ultraviolet stability. (1st December 2022) - Zhu, Xueliang; Lau, Cho Fai Jonathan; Mo, Kangwei; Cheng, Siyang; Xu, Yalun; Li, Ruiming; Wang, Cheng; Zheng, Qixian; Liu, Yong; Wang, Ti; Lin, Qianqian; Wang, Zhiping
Abstract: Long-term stability remains a challenge for commercializing metal halide perovskites in photovoltaic (PV) applications. Ultraviolet-induced degradation (UV-ID) has been considered as one of the key stability issues for crystalline silicon PVs. However, limited studies have been performed on the long-term UV-ID of perovskite PVs, and none has been found related to operational stability under UV stressing. Here, we focus on UV-ID of inverted perovskite solar cells that comprise nickel oxide (NiO) as the hole transporting layer. Under continuous UV irradiation, we observe vacancies/voids generated in the vicinity of NiO/perovskite heterojunction. Time-resolved femtosecond transient absorption and double-ion injection current measurements indicate UV irradiation would induce interface shallow traps and severe ion migration. These UV-induced degradations can be greatly suppressed by modifying the heterojunction with a self-assembled monolayer [2-(9 H-Carbazol-9-yl)ethyl] phosphonic acid (2PACz). Unencapsulated NiO/2PACz devices, operated at maximum power point (MPP), retain over 90% of their initial efficiency after exposing to a total UV dose of 35 kWh/m 2 . The best-performing device reaches a stabilized efficiency of 22.2%, and retains 82% of its original efficiency after 2000 h of MPP tracking under one sun illumination (100 mW/cm 2 ) at 45 ℃ in ambient air when encapsulated. Graphical Abstract: ga1 Highlights: 2PACz modification inhibits UV-induced deprotonation and vacancy formation near NiO/perovskite interface. The PCE is improved from 19.9% to 22.4% by interface passivation. 2PACz modification greatly improves operational stability under UV aging. Encapsulated NiO/2PACz devices sustain 82% after 2000 h MPP tracking under one sun illumination.